PERAN GURU AGAMA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA N 1 KEP. PONGOK - Unik Hanifah Salsabila; Karina Karina (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2021)
Educators are ready to oversee learning as well as should have the option to make and keep up with ideal learning conditions for the accomplishment of instructing destinations. So the educator's job is required in working on the nature of Islamic Religious Education learning. (1) To discover the job of strict instructors as teachers in working on the nature of learning in Islamic Religion subjects in… .. (2) To discover the job of strict educators as instructors in working on the nature of learning in Islamic Religion subjects at SMA N 1 kep. pongok (3) To knowing the job of strict instructors as coaches in working on the nature of learning in Islamic subjects in SMA N 1 kep. Pongok This kind of exploration is subjective examination. Information were gathered utilizing perception, meeting, and documentation techniques. After the creators directed the exploration, the outcomes were as per the following: (1) The job of strict instructors as teachers in working on the nature of Islamic learning is by giving inspiration and genuine guides to understudies, expanding educator understanding and information, and showing their insight with tolerance. (2) The educator's job as an instructor in working on the nature of Islamic learning is by making understudies more basic or having high friendly connection, utilizing exceptional and fascinating techniques, just as by evaluating the material and summing up it again to recollect understudies' reasoning force. (3) The job of the instructor as a coach in working on the nature of Islamic learning is by giving freedoms to understudies to counsel different hardships or issues looked by their understudies, educators give task strain to understudies, instructors complete appraisals, and make great and fun learning circumstances with the goal that they don't exhausting.